SYSTEM OF MODEL FOR TRAINING FUTURE MASTERS OF TOURISM, AS WELL AS THE ALGORITHM OF ITS PRODUCTIVE IMPLEMENTATION IN HIGHER EDUCATION - Larisa Beskorovaynaya (Kherson State University, 2017)
On the basis of theoretical analysis author substantiates the system model of training future masters of tourism in higher education. The author found the methodological basis of preparation of future tourism masters in the field of higher education. In addition, theoretically grounded and model of the system of training of future masters of tourism, opened its components, a set of organizational and pedagogical conditions. System model of professional training of future masters of tourism in higher education, which is considered by us as an open, integrative, multi, mobile, adequate social requirements and individual needs of students, the educational system contains components: theoretical, methodological, structural and functional, design and technology, analytical criterion. The author proved that the model provides the opportunity to reflect, recreate individual readiness of future masters of tourism with a view to understanding its forecasting features, operation and further successful implementation in educational practice.The author researched and proposed algorithm productive use of the system model of training future tourism masters in the field of higher education. Based on the results of research made a some conclusion. Further prospective research directions are also provided.